2016
DOI: 10.1007/s00343-016-5034-0
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of body weight and resistance to ammonia in the Pacific white shrimp Litopenaeus vannamei juveniles

Abstract: A bstractAmmonia, toxic to aquaculture organisms, represents a potential problem in aquaculture systems, and the situation is exacerbated in closed and intensive shrimp farming operations, expecially for Litopenaeus vannamei . Assessing the potential for the genetic improvement of resistance to ammonia in L . vannamei requires knowledge of the genetic parameters of this trait. The heritability of resistance to ammonia was estimated using two descriptors in the present study: the survival time (ST) and the surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 51 publications
1
10
1
Order By: Relevance
“…In order to know how much of the trait of ammonia tolerance in L . vannamei is genetically involved based on the additive genetic effect model, we estimated the heritability of ammonia tolerance with these families [ 38 ]. Before the heritability estimation, we carried out a pre-experiment to detect the half-lethal time under our experiment condition with the ammonia doses reported by Sun et al [ 39 ], because the toxicity of ammonia is largely depend on temperature, pH, salinity, and body weight, etc.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to know how much of the trait of ammonia tolerance in L . vannamei is genetically involved based on the additive genetic effect model, we estimated the heritability of ammonia tolerance with these families [ 38 ]. Before the heritability estimation, we carried out a pre-experiment to detect the half-lethal time under our experiment condition with the ammonia doses reported by Sun et al [ 39 ], because the toxicity of ammonia is largely depend on temperature, pH, salinity, and body weight, etc.…”
Section: Methodsmentioning
confidence: 99%
“…During the acclimation, the holding water conditions were as follows: salinity at 30‰, pH at 7.9 ± 0.1, temperature at 27 ± 0.5°C, and oxygen higher than 6 mg/L. After the acclimation, one group was treated as the control (LV_C), and the other group (LC_E) was challenged with high-concentration ammonia (~ 62.23 mg/L) according to our previous study [ 38 ]. The temperature was 27 ± 0.5°C, pH was 7.9 ± 0.1, and salinity was 30‰.…”
Section: Methodsmentioning
confidence: 99%
“…Fortunately, a total of 25,772 SNPs were found from these genes, which providing important candidate markers for association study. In addition, we have accumulated some groups with significantly different performance on ammonia tolerance [20,42]. Consequently, as an alternative approach to QTL mapping, we used a marker-trait association analysis to identified SNP markers that associated with ammonia tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Its base population was produced with seven commercial L. vannamei strains that were separately introduced from America and Singapore with an incomplete diallel cross experiment in 2011 at the Mariculture Genetic Breeding Center of the Chinese Ministry of Agriculture (Qingdao, Shandong province, China). A total of 1849 individuals (average body weight was 3.1 g) from 52 full-sib families of the population were performed ammonia stress test at Qingdao in 2013, and their survival time ranged from 65 to 218 h. The detail information for the shrimps and stress process could be found in our previous study [42]. The 60 first-dead individuals (as ammonia-sensitive group, AS 1 ) and the 60 last-dead individuals (as ammonia-tolerant group, AT 1 ) were used for identification of associated SNP markers.…”
Section: Shrimp Populations For Association Analysis and Samplingmentioning
confidence: 99%
“…However, in a long-term trial with extreme high temperature, Chang et al [2016] demonstrated that survival varied significantly among the families of S. intermedius. That genetic factors play important roles in survival has also been concluded for other aquatic animal species Li et al, 2016;Thoa et al, 2015;Thoa, Ninh, Knibb, & Nguyen, 2016). Moreover, in S. intermedius, completely different culture methods or diets caused significant family by environment interaction effects on growth traits (Wang et al, 2015;Zhang et al, 2013).…”
mentioning
confidence: 90%